Heterosis for yield and related component traits in castor (Ricinus communis L.): HETEROSIS FOR YIELD AND RELATED COMPONENT TRAITS IN CASTOR - SHALINI RAGHUWANSHI; RAMESH; RAHUL BHARDWAJ; MOOLA RAM; MANISH KUMAR; NETAJIT SINGH (Journal of Oilseeds Research, 2023)
Investigating the potential of castor as a leading non-edible oil crop, this study focused on evaluating the heterosis of eight true inbred lines via a diallel crossing approach, resulting in the development of 28 hybrids. Through a randomized block design with three replications at Agricultural Research Station (ARS), Mandor, Agriculture University, Jodhpur, during the kharif season of 2022, these hybrids and their parental lines, alongside the standard check GCH-8, were rigorously assessed. Notably, two hybrids viz., PVT-4 × MCI-8 and MP-11-17× PVT-7 demonstrated significant heterosis, showcasing 30.44% and 21.78% increased seed yield per plant, respectively, in comparison to the standard check GCH-8. This highlights the promising prospects of castor as an economically viable annual crop with high seed yield potential.